O tempo e o espaço na construção do ensino religioso: um estudo sobre a concepção do ensino religioso na Lei de Diretrizes e Bases da Educação Nacional - Stigar, Robson (2009)
The object of this research is to analyze the design of religious education in the current Law of Guidelines and Bases of Education. The hypothesis that this research is to introduce the concept of religious education provided in Article 33 of the current conception would LDB "mixed" and consists of a composition of several current and interests. Indeed there is considerable ambiguity in the wording of Article 33 of the current design of the LBD on Religious Education and its deliberations. The wording of Article 33 of the current Law of Directives and Bases of National Education has many difficulties with respect to their identity, especially as to the content curriculum, due to its ambiguity. I make the assumption that the current wording of Article 33 of that Act would have been an exit strategy and policy to please the various religious groups and nonreligious in the Brazilian society, especially the CNBB, the FONAPER, the evangelicals, other religious institutions and also the group does not own, which argues for the exclusion of religious education at school. These currents, which were present in the lobbies Congress, led to a consensus of law, by nature ambiguous, reflecting their divergent interests. The solution to present to resolve these ambiguities and overcome the malaise of the discipline of religious education is the integration of the Science of Religion as a new model for the discipline of religious education. We propose the study of secular and religious phenomenon as any other knowledge inscribed in the sphere of science that are taught in schools. We propose the adequate training of professionals with all the care that is waived for the training of professional of any other area insisted that the object of this study should be the training of citizens and not the conversion of disciples